The exclusion of Jews in the Norwegian Constitution of 1814 : origins – contexts – consequences - Hoffmann, Christhard 1952- HerausgeberIn; Metropol-Verlag (Studien zum Antisemitismus in Europa, 2016)
Preface / Guri Hjeltnes -- Introduction / Christhard Hoffmann -- The Politics of Jewish Emancipation in Europe at the Beginning of the Nineteenth Century / Reinhard Rürup -- The Ban on Jews in the Norwegian Constitution / Håkon Harket -- Constitutional Discourse and Anti-Judaism : Friedrich Buchholz and Christian Magnus False / Iwan Michelangelo D'Aprile, Håkon Harket -- The "Jewish Feud" in Denmark 1813 / Therkel Stræde -- Societal Change, Economic Decline and National Identity : The Debate about Jews in Sweden in the Early Nineteenth Century / Henrik Edgren -- The Practise of Exclusion : How Article 2 in the Norwegian Constitution was Administered and Enforced between 1814 and 1851 / Frode Ulvund -- The 1942 Reinstatement of the Ban on Jews in the Norwegian Constitution / Bjarte Bruland